An algorithm of semi-Delaunay triangulation of points cloud scattered on surface - Kucwaj, Jan (Computer Science, 2014)
The purpose of the paper is to generalize the Delaunay triangulation onto surfaces. A formal definition and appropriate algorithm are presented. Starting from plane domain Delaunay triangulation definition a theoretical approach is evolved which is a background for further considerations. It is proved that in case of plane surface the introduced Delaunay triangulation of surfaces is identical with classical Delaunay triangulation of plane domain. The proposed algorithm is implemented and numerical results are shown.